Cutter Path Strategies For Shoulder Milling Of Thin Deflecting Walls - Raja Abdullah, Raja Izamshah; Hassan, Zulhairy; Kasim, Mohd Shahir; Abu Bakar, Mohd Hadzley; Md Ali, Mohd Amran; Sulaiman, Mohd Amri; Subramonian, Sivarao (Trans Tech Publications, 2014)
-